Os arquitetos não-alinhados: contrapontos entre o contexto, discurso e a produção de um grupo de arquitetos paulistas (1977-1985) - Lopes, Matheus Franco da Rosa (2018)
The present work is an investigation with historical and architectural focus on the group of architects of São Paulo denominated in 1982 as the "nãoalinhados". It seeks a better understanding of the relations of the nomenclature given with that historical moment, establishing a panorama of time, mainly through some contests promoted by the IAB/SP and analysis of the relationships between the projects developed, the context and the critical discourse legitimating a new practice. The não-alinhados were a group assembled by the magazine Project for a discussion on the directions of Brazilian architecture; it was composed of seven architects who, through distinct strategies and motivations, were developing an out-of-the-standard production of an architecture that was called "escola paulista", although this term will acquire contradictions and variations in the course of this work. This event gains more notoriety since it’s realized in a period considered by the historiography of architecture as a period of revision or renovation. Therefore this analysis contributes to a better understanding of the architectural productions developed in the period and events that gradually added up to configure changes in the panorama of Brazilian architecture, in the sense of a greater acceptance of multiple paths.